2006
DOI: 10.1073/pnas.0605053103
|View full text |Cite
|
Sign up to set email alerts
|

Day-to-day dynamics of experience–cortisol associations in a population-based sample of older adults

Abstract: In 156 older adults, day-to-day variations in cortisol diurnal rhythms were predicted from both prior-day and same-day experiences, to examine the temporal ordering of experience-cortisol associations in naturalistic environments. Diary reports of daily psychosocial, emotional, and physical states were completed at bedtime on each of three consecutive days. Salivary cortisol levels were measured at wakeup, 30 min after awakening, and at bedtime each day. Multilevel growth curve modeling was used to estimate di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
635
7
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 665 publications
(709 citation statements)
references
References 49 publications
50
635
7
3
Order By: Relevance
“…This supports an effect identified in previous research (Adam et al, 2006), however, Adam et al demonstrated an effect of the S1 on same-day physical symptoms rather than the CAR AUCi.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This supports an effect identified in previous research (Adam et al, 2006), however, Adam et al demonstrated an effect of the S1 on same-day physical symptoms rather than the CAR AUCi.…”
Section: Discussionsupporting
confidence: 90%
“…Model 2 was based on that of Adam et al (2006), who entered prior-and same-day physical symptoms simultaneously into a model predicting morning cortisol, in order to determine which variable was more strongly associated with the CAR. Here, physical symptoms and daily affect were entered separately into models predicting the CAR: Finally, a between-subjects analysis was carried out.…”
Section: Analytic Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…This interpretation is supported by the enlarged adrenal glands in young adult highlocomotion females. Further studies are required to address other physiological repercussions that may exist later in life as a result of this differential HPA axis activity, and to determine the extent to which HPA axis activity is a stable trait within individuals over time (Adam et al, 2006;Burleson et al, 2003;Capitanio et al, 1998;Cohen and Hamrick, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…• Diminished physical activity 13 • Diminished motor function 14,15 • Symptoms of depression 16 • Disrupted sleep and daytime dysfunction 17 • Impaired mental and cognitive function 18 • Increased systolic blood pressure 19 • Increased sympathetic tone and vascular resistance 20,21 • Increased hypothalamic pituitary adrenocortical activity 22,23 • Altered gene expression related to anti-inflammatory responses 24 • Altered immunity 25,26 Of greater concern, however, is an accumulating volume of research that highlights loneliness as a risk factor for both functional decline as well as increased mortality. 4,8,[27][28][29] In short, there is evidence that the subjective experience of loneliness can significantly contribute to premature death independently of other physical, behavioral, or psychological factors.…”
Section: Effects Of Lonelinessmentioning
confidence: 99%